Co-occurrence patterns of esophageal and stomach cancer across 204 countries and territories: a spatial correspondence and systematic analysis - Qin, Yanru; Xu, Jiayao; Gong, Jiabei; Han, Huiqiong; Wang, Zehua; Wang, Wenjia; wang, Lei; Sui, Xin; Chen, Guanyu; Jia, Yongxu (Frontiers in Oncology, 2025)
BackgroundEsophageal and gastric cancers are common malignant tumors of the digestive tract worldwide, characterized by a substantial disease burden and significant regional disparities. While these cancers share anatomical proximity, risk factors, and pathogenic mechanisms to some extent, there remains a lack of comprehensive and up-to-date global comparative studies on their co-occurrence patterns and burden trends.MethodsUsing primary data from the Global Burden of Disease (GBD) 2021 study, we defined and categorized global co-occurrence patterns of esophageal and gastric cancers based on quartile methods. Descriptive analysis, correlation analysis, age-period-cohort modeling, decomposition analysis, and predictive modeling were employed to thoroughly examine the disease burden of both cancers across 204 countries and territories from 1990 to 2021.ResultsThe disease burden of gastric cancer consistently exceeded that of esophageal cancer in most countries and regions. Spatially, the Eastern and Northern Hemispheres, including countries such as China and Mongolia, were identified as consistent high-burden regions for both cancers. In contrast, the Western and Southern Hemispheres were predominantly characterized by single-cancer dominance or low-burden patterns. Disease burden was negatively correlated with the Socio-demographic Index (SDI), with higher burden observed in low-SDI regions. Males and older populations faced elevated disease risks. Furthermore, population growth and aging were identified as major drivers increasing the overall burden. Predictions indicate that by 2031, the age-standardized rates of both cancers will continue to decline, yet the overall burden of gastric cancer will remain significantly higher than that of esophageal cancer.ConclusionsGastric cancer imposes a heavier disease burden than esophageal cancer across most countries and regions. These findings underscore the necessity for sustained and targeted prevention strategies, such as the promotion of healthy lifestyles, enhanced early screening, and improved healthcare accessibility in high-burden regions, to effectively reduce the global burden of esophageal and gastric cancers.